1991
DOI: 10.1111/j.1399-0004.1991.tb03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Holt‐Oram syndrome in four half‐siblings with unaffected parents: brief clinical report

Abstract: The Holt‐Oram syndrome was diagnosed in four offspring of three mothers and the same unaffected father. One additional child lacked the characteristic clinical features of the Holt‐Oram syndrome. In contrast to the general autosomal dominant inheritance with complete penetrance, our observation suggests a paternal mutation, resulting in mosaicism, probably restricted to the germline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…On the other hand, PreP as an apparently single anomaly, could be the only visible defect of some of the recognized autosomal dominant conditions such as the Holt Oram syndrome, where a mild and therefore overlooked heart defect could lead to its misdiagnosis. To our knowledge, advanced PA has not been mentioned in association with Holt Oram, although a relationship could be indirectly inferred (Barisic et al, 2014; Braulke et al, 1991). In a study on Townes Brocks, another syndrome of autosomal dominant inheritance that includes anus atresia and PreP among its features, Böhm et al (2006) demonstrated the paternal origin of the mutation in 14 of their 16 cases, without an obvious PA effect.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, PreP as an apparently single anomaly, could be the only visible defect of some of the recognized autosomal dominant conditions such as the Holt Oram syndrome, where a mild and therefore overlooked heart defect could lead to its misdiagnosis. To our knowledge, advanced PA has not been mentioned in association with Holt Oram, although a relationship could be indirectly inferred (Barisic et al, 2014; Braulke et al, 1991). In a study on Townes Brocks, another syndrome of autosomal dominant inheritance that includes anus atresia and PreP among its features, Böhm et al (2006) demonstrated the paternal origin of the mutation in 14 of their 16 cases, without an obvious PA effect.…”
Section: Discussionmentioning
confidence: 93%
“…Also mutations located outside the T-box domain show a similar genotype-phenotype correlation, determining predominantly heart or limb defects according to the mutation. Germinal mosaicism has also been reported in one case report in which an unaffected man fathered 4 offspring with HOS by 3 different women [ 116 ]. Although no other cases have been described in the literature, we have found a family with 2 affected offspring from unaffected parents.…”
Section: Mendelian Formsmentioning
confidence: 88%
“…It is considered 100% penetrant with varying expressivity in the heart and upper extremity [ 10 ]. However, incomplete penetrance [ 11 ], lack of penetrance [ 12 ], somatic mosaicism [ 12 ], and probable germinal mosaicism [ 13 ] have also been reported for this disease. The majority of the patients suffer from this syndrome due to de novo mutations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%